2007
DOI: 10.1096/fj.06-7248com
|View full text |Cite
|
Sign up to set email alerts
|

A murine model of hyperdopaminergic state displays altered respiratory control

Abstract: The dopamine transporter (DAT) protein plays an important role in the termination of dopamine signaling. We addressed the hypothesis that loss of DAT function would result in a distinctive cardiorespiratory phenotype due to the significant role of dopamine in the control of breathing, especially with respect to chemical control, metabolism, and thermoregulation. The DAT knockout mouse (DAT-/-) displays a state of functional hyperdopaminergia characterized by marked novelty driven hyperactivity. Certain behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 35 publications
(63 reference statements)
4
19
0
1
Order By: Relevance
“…This failure of regulation leads to a hyperdopaminergic state, which causes the violent behavior, delirium, agitation, and sudden death when the neurocardiac axis is activated. A dopamine transporter murine model of hyperdopaminergic state displays a distinctive cardiorespiratory and thermal phenotype, providing further support for the altered dopamine regulation hypothesis of excited delirium [39].…”
Section: Discussionmentioning
confidence: 73%
“…This failure of regulation leads to a hyperdopaminergic state, which causes the violent behavior, delirium, agitation, and sudden death when the neurocardiac axis is activated. A dopamine transporter murine model of hyperdopaminergic state displays a distinctive cardiorespiratory and thermal phenotype, providing further support for the altered dopamine regulation hypothesis of excited delirium [39].…”
Section: Discussionmentioning
confidence: 73%
“…The reaction to the hypoxia condition is reduced in DAT-KO mice, compared to wild-type (WT) mice while CO2 production does not differ in mutants (Vincent et al, 2007). Also, an alteration in body temperature of DAT-KO mice was found.…”
Section: Dat Knockout (Dat-ko) Micementioning
confidence: 99%
“…Also, an alteration in body temperature of DAT-KO mice was found. Circadian measurement showed that they have lower body temperature during resting time (daylight time) (Vincent et al, 2007). The involvement of DAT in thermoregulation is also supported by studies of methylone-induced lethality that is thought to be related to body hyperthermia.…”
Section: Dat Knockout (Dat-ko) Micementioning
confidence: 99%
“…DA agonism in the preoptic area triggers increased heat loss, which is blocked by DA antagonists and which reduces the ability of rats to accommodate to a heat load,74 probably D2 mediated 75. DA transporter knockout mice (DAT−/−) display functional hyperdopaminergia and hyperactivity; their body temperature is significantly lower than normal mice during inactive periods 76…”
Section: Measurement and Definition Of Hyperthermiamentioning
confidence: 99%